LITERATURE ANALYSIS ON ECONOMIC AND SOCIAL INEQUALITY: TRENDS, CAUSES, AND SOLUTIONS - Loso Judijanto (Adisam Publisher, 2025)
Economic and social inequality is an issue that has been increasingly observed in recent decades, with significant impacts on economic growth and social stability. This literature analysis explores global inequality trends, identifies its main causes, and evaluates proposed solutions to address the problem. Factors such as globalisation, technological development, unfair government policies, and discrimination contribute to the widening gap between rich and poor groups. Meanwhile, potential solutions include progressive tax reform, improved access to education and healthcare, decent job creation, and stronger labour protection. By adopting a comprehensive and integrative approach, the right policies can help reduce inequality and promote more equitable welfare in society.